An overview of consumption culture from the master-slave dialectic - TÜZÜN, SÜMEYRA (My University, 2023)
The understanding that causes cultural codes to be replaced by universal capitalist consumption codes permeates our lives through advertisements. While consumption is the purchase of a material commodity, it has now evolved into a direction loaded with spiritual feelings and values. Today, it is seen that consumption has shifted from the consumption of essential needs to luxury consumption. The master-slave dialectic that emerged as a result of the demands for mutual acceptance in Hegel similarly shows the efforts of institutions to seek suitors for their product advertisements to increase their profits. At the individual level, people can make themselves visible through the products they use. This study aims to explain how the ideals of increasing consumption are realized through communication, basing the epistemological roots of the increase in luxury consumption on Hegel. Within the scope of the study, personal care and accessory advertisements on national television channels will be shown. The study will be examined using the semiotic analysis method. In the study, only advertisements broadcast on national general channels will be included, internet advertisements, viral advertisements and outdoor advertisements will not be included. In the products shown in the sample advertisements, emotional manipulation is carried out with themes such as being admired, coming to the fore, freedom, being envied, and being special. They are the products offered in advertisements, but with those products, what is desired is peace, love, prestige, a challenge, being admired and at the forefront. As a result, when we adapt Hegel's master-slave dialectic to consumption culture, we encounter an image where institutions become masters and consumers become slaves.
Keywords: Communication; Consumption; Needs; The Master-Slave Dialectic